2007
DOI: 10.1029/2006jc003698
|View full text |Cite
|
Sign up to set email alerts
|

On long baroclinic Rossby waves in the tropical North Atlantic observed from profiling floats

Abstract: Along-shore wind fluctuations and an equatorially forced coastal Kelvin wave were found to be responsible for the excitation of annual-and semiannual-propagating Rossby waves in the eastern subbasin. These waves are transmitted along a waveguide formed by the African shelf and the MAR. The speed of their propagation varies in magnitude and direction because of bottom topography and irregularity of the coastline. Unstable standing Rossby waves with annual and semiannual periods are shown in both the subbasins. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 58 publications
(91 reference statements)
1
29
2
2
Order By: Relevance
“…The vertical structure found by Chu et al (2007) used temperature data from ARGO floats in the North Atlantic and as a result is quite different to those found here with a pronounced sub-surface maximum at 1500 m and zero ampli- tude at the surface. Their findings showed a large contribution from the second baroclinic mode in the structure, but did display a similarity to the U -BPD profile with an inversion seen in the top 200 m, which is not seen in the model profiles here.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…The vertical structure found by Chu et al (2007) used temperature data from ARGO floats in the North Atlantic and as a result is quite different to those found here with a pronounced sub-surface maximum at 1500 m and zero ampli- tude at the surface. Their findings showed a large contribution from the second baroclinic mode in the structure, but did display a similarity to the U -BPD profile with an inversion seen in the top 200 m, which is not seen in the model profiles here.…”
Section: Discussioncontrasting
confidence: 92%
“…Chu et al (2007) used data from ARGO floats in the North Atlantic to extract vertical profiles of Rossby waves. They found that the second baroclinic mode was always dominant, with the contributions of other modes geographically variable.…”
Section: F K Hunt Et Al: the Vertical Structure Of Oceanic Rossby mentioning
confidence: 99%
“…This slow signal transfer across the North Atlantic is in the same order as the magnitude of Rossby Wave propagation. With a typical wave speed of 10-15 cm·s −1 [42] the NAO induced SST pattern in the region of the AF needs one to two years to reach the west coast of the Atlantic where the drift of the Gulf Stream is observed. Much lower wave speeds have been quantified by ref.…”
Section: The Front's Impact On the Gulf Streammentioning
confidence: 99%
“…Applications of Argo data have included analysis of ocean Rossby waves (Chu et al 2007) and deep seasonal temperature variations (Hosoda et al 2006). Recently, the high temporal resolution of the Argo data was used to show that the temperature structure of an equatorial Kelvin wave in the Pacific, forced by a particular MJO event, extended down to at least 1500 m depth (Matthews et al 2007), deeper than expected from theoretical considerations (Johnson and McPhaden 1993).…”
Section: Introductionmentioning
confidence: 99%